The long non-coding RNA Meg3 is dispensable for hematopoietic stem cells - Sommerkamp, Pia; Hotz-Wagenblatt, Agnes; Trumpp, Andreas (Scientific reports, 2019)
The long non-coding RNA (lncRNA) Maternally Expressed Gene 3 (Meg3) is encoded within the imprinted Dlk1-Meg3 gene locus and is only maternally expressed. Meg3 has been shown to play an important role in the regulation of cellular proliferation and functions as a tumor suppressor in numerous tissues. Meg3 is highly expressed in mouse adult hematopoietic stem cells (HSCs) and strongly down-regulated in early progenitors. To address its functional role in HSCs, we used MxCre to conditionally delete Meg3 in the adult bone marrow of Meg3mat-flox/pat-wt mice. We performed extensive in vitro and in vivo analyses of mice carrying a Meg3 deficient blood system, but neither observed impaired hematopoiesis during homeostatic conditions nor upon serial transplantation. Furthermore, we analyzed VavCre Meg3mat-flox/pat-wt mice, in which Meg3 was deleted in the embryonic hematopoietic system and unexpectedly this did neither generate any hematopoietic defects. In response to interferon-mediated stimulation, Meg3 deficient adult HSCs responded highly similar compared to controls. Taken together, we report the finding, that the highly expressed imprinted lncRNA Meg3 is dispensable for the function of HSCs during homeostasis and in response to stress mediators as well as for serial reconstitution of the blood system in vivo.
Gesehen am 31.07.2019